Mesophotic reefs offer thermal refuge to the 2023 Caribbean mass bleaching event in the Cayman Islands - Gretchen Goodbody-Gringley; Alex D. Chequer (Scientific Reports)
Abstract Coral reefs are increasingly threatened by marine heatwaves, which drive widespread coral bleaching and mortality. Mesophotic coral ecosystems (MCEs) have been proposed as potential thermal refuges due to their greater depth and relative isolation from surface temperature extremes. Yet their resilience to extreme heat events remains uncertain, with location specific conclusions, thus requiring further studies. Here, we investigate the effects of the 2023 marine heatwave in the Cayman Islands, which resulted in prolonged sea surface temperatures exceeding 31 °C and 17.5 DHW with extensive bleaching across shallow coral reefs. Utilizing vertical transect surveys from 10 m to 50 m, we assessed depth-related variations in bleaching prevalence and temperature profiles. Our results indicate a significant decline in bleaching with increasing depth, with a concurrent reduction in temperature. Depth-generalist species exhibited reduced bleaching at greater depths, whereas shallow-water specialists displayed severe bleaching. These findings suggest that while MCEs may provide thermal refuge for some species, their capacity to buffer against climate-driven reef degradation is species-specific. Given the increasing frequency and intensity of marine heatwaves, understanding the role of deeper reef habitats in mitigating coral loss is critical for informing conservation and management strategies. Our study underscores the importance of protecting MCEs as potential thermal refuges while emphasizing the need for continued research on species-specific thermal resilience with depth.